Kebijakan Sertifikasi Guru Dalam Peningkatan Kualitas Pengajaran Dan Motivasi Guru - Dian Pratiwi Br. Marpaung; Nurroyian N; Fachri Habib; Ahmad Rinaldi Siregar; Tengku Darmansah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Teacher certification, which is implemented as part of education reform efforts, is expected to increase teacher professionalism through recognizing competence and providing financial incentives. This research uses a literature review method which is based on book and other journal references. This research aims to analyze the impact of teacher certification policies on improving the quality of teaching and work motivation of teachers in Indonesia. The results of the research show that the certification policy has a positive influence on the quality of teacher teaching, which can be seen from the increased use of active learning methods, the preparation of more structured learning plans, and more effective learning evaluation. In addition, the financial incentives provided through the certification program also increase teacher work motivation, although there are challenges in terms of distribution of allowances and sustainability of post-certification training. These findings also reveal differences in the impact of certification policies on teachers in urban and rural areas, which are influenced by factors of resource accessibility and institutional support.